Rising incidence of late‐stage head and neck cancer in the United States. Issue 5 (13th November 2019) - Thompson‐Harvey, Adam; Yetukuri, Mahi; Hansen, Alec R.; Simpson, Matthew C.; Adjei Boakye, Eric; Varvares, Mark A.; Osazuwa‐Peters, Nosayaba
Abstract : Background: The current study was conducted to determine whether the incidence of late‐stage head and neck cancer (HNC) is decreasing and to estimate the risk of late‐stage HNC diagnosis based on race and sex. Methods: Age‐adjusted incidence rates for patients aged ≥18 years with stage IV HNC were abstracted from the Surveillance, Epidemiology, and End Results database (2004‐2015). Rates were stratified by race, sex, and age. Joinpoint regression estimated annual percent changes (APCs) in rates over time, and logistic regression estimated adjusted odds ratios (aORs). Results: There were 57, 118 patients with stage IV HNC in the current study cohort, with an average age of 61.9 years. From 2004 to 2015, the age‐adjusted incidence rates for stage IV HNC significantly increased by 26.1% (6.11 per 100, 000 person‐years in 2004 to 7.70 per 100, 000 person‐years in 2015). White and Asian/Pacific Islander/American Indian/Alaska Native patients had significant increases in incidence (APC for white patients, 3.03 [ P  < .01] and APC for other races, 1.95 [ P  < .01]), whereas rates among black patients remained stable but were highest across racial groups. Incidence was higher among males compared with females. When restricted only to patients with stage IVC (metastatic) HNC, there remained a significant increase in incidence, especially for oropharyngeal cancer, which showed a 22.9% increase (0.21 per 100, 000 person‐years in 2004 vs 0.25 per 100, 000 person‐years in 2015). Despite a decreasing overall incidence of stage IV HNC in black patients (aOR, 1.28; 95% CI, 1.22‐1.34) they, along with males (aOR, 3.95; 95% CI, 3.80‐4.11), had significantly increased risks of being diagnosed with late‐stage HNC. Conclusions: There is an increasing incidence of late‐stage HNC in the United States, with male patients and black individuals faring the worst. Abstract : Contrary to the goals of the Healthy People 2020 initiative, the incidence of late‐stage head and neck cancer is increasing in the United States. This increasing incidence appears to be driven by males and the diagnosis of oropharyngeal cancer.